1997
DOI: 10.1242/jeb.200.5.941
|View full text |Cite
|
Sign up to set email alerts
|

Nervous Control of Male Sexual Drive in The Hermaphroditic Snail Lymnaea Stagnalis

Abstract: We studied the role of the prostate gland in determining the level of male sexual drive in the hermaphroditic pond snail Lymnaea stagnalis. Male sexual drive is high after a period of social isolation and decreases after copulation as a male. A positive correlation exists between the level of male sexual drive and the volume of the prostate gland. Like male sexual drive, the volume of the prostate gland increases during a period of social isolation and decreases after copulation as a male. Behavioural experime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

1998
1998
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(12 citation statements)
references
References 27 publications
0
12
0
Order By: Relevance
“…Previous work has shown that one week of isolation suffices to fully replenish the components of ejaculate in this species, increasing their male mating motivation (Van Duivenboden and Ter Maat 1985;De Boer et al 1997). Thus, we are confident that snails in 28 °C treatment did not fully replenish their sperm reserves.…”
Section: Discussionmentioning
confidence: 58%
See 2 more Smart Citations
“…Previous work has shown that one week of isolation suffices to fully replenish the components of ejaculate in this species, increasing their male mating motivation (Van Duivenboden and Ter Maat 1985;De Boer et al 1997). Thus, we are confident that snails in 28 °C treatment did not fully replenish their sperm reserves.…”
Section: Discussionmentioning
confidence: 58%
“…We designed the experiment with the aim to measure the consequence of heat on spermatogenesis, even though this species continuously produces sperm after maturation. sPrevious work has shown that one week of isolation suffices to fully replenish the components of ejaculate in this species, increasing their male mating motivation (Van Duivenboden and Ter Maat 1985; De Boer et al 1997). Thus, we are confident that snails in 28 °C treatment did not fully replenish their sperm reserves.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the study of De Boer et al (1996), we hypothesized that only the fourth category, 'long interactions', reflected copulation behavior, but the eversion of the preputium and intromission were very difficult to see due to the small size of R. balthica. Moreover, it has been shown that isolation may facilitate the monitoring of social interactions (more copulations and a shorter total copulation sequence) (Van Duivenboden and Ter Maat, 1985) but it may also disturb other parameters such as the willingness of snails to mate as a male role (Boer et al, 1997) and the quantity of sperm transferred by the sperm donor (Loose and Koene, 2008). To optimize the monitoring of copulation behavior, it would be relevant to use optimal conditions that have already been determined for the observation of the reproduction of small gastropod species, such as Physa acuta and Radix auricularia (Facon et al, 2006;Swart et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…To do so, we let the snails copulate, then measured SFP gene expression at 3, 24, 48, and 192 h after mating using reverse-transcription quantitative PCR (qPCR). Monitoring for 1 week after mating is considered reasonable since these snails become highly motivation to copulate as male after 8 days of social isolation (Van Duivenboden & Maat, 1985), and the fullness of the prostate gland is the main driver of this motivational state (De Boer et al, 1997). Moreover, it has been shown that this species increases the production of one of the known SFPs, LyAcp10, 1 day after mating (Swart et al, 2019).…”
Section: Introductionmentioning
confidence: 99%